2013
DOI: 10.31729/jnma.572
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile, Aetiology and Outcome of Afebrile Seizures in Children

Abstract: Introduction: Clinical and outcome profiles of childhood seizures can be different in resource limited settings where neurologists face lots of challenges in diagnosis and management of seizure. This study was conducted to investigate the clinical profile, causes and outcome of afebrile seizures in children in resource limited settings. Methods: This was a prospective hospital based study. Children with afebrile seizures were followed up with exclusion of febrile and acute provoked seizures. Clinical, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
3
8
0
Order By: Relevance
“…). The incidence of neuroimaging abnormality compared too many other studies such as those done by Poudel et al, Rasool et al, Kalnin et al, Mathur et al, Mohammadi et al which showed neuroimaging abnormality to be around 27 % to 35% in new onset afebrile seizures 6,10,[15][16][17]. Of the 65 patients in the present study, 22 had neuroimaging abnormality and 16 had abnormalities on neurological examination.…”
supporting
confidence: 41%
See 1 more Smart Citation
“…). The incidence of neuroimaging abnormality compared too many other studies such as those done by Poudel et al, Rasool et al, Kalnin et al, Mathur et al, Mohammadi et al which showed neuroimaging abnormality to be around 27 % to 35% in new onset afebrile seizures 6,10,[15][16][17]. Of the 65 patients in the present study, 22 had neuroimaging abnormality and 16 had abnormalities on neurological examination.…”
supporting
confidence: 41%
“…This might be due to birth asphyxia, neurocysticercosis and nervous system infections and other risk factors. 6,7 The basis of incidence can be evaluated by EEG. It is mostly useful in investigating afebrile epileptic seizures and its risk of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Structural etiologies were the most common, accounting to 66.11%, followed by metabolic in 12.39%, unknown etiology in 8.26%, infection sequelae in 6.61%, hot water epilepsy in 4.95%, and immune etiology in 0.82%. Most common structural cause of seizures was secondary to hypoxic-ischemic insult/perinatal insult (38%), which was similar to a study carried out by Poudel et al ,[15] who found that birth asphyxia (12%) was the most common cause of afebrile seizure followed by neurocysticercos (8.8%), sequel of CNS infection (6.5%), and cerebral malformation (7.1%). In this study, metabolic causes were the second most common with Leigh syndrome being the frequent cause [Table 2].…”
Section: Discussionsupporting
confidence: 87%
“…12,13 The rates of epileptiform discharges varied from 44 to 80% in children who were admitted with seizures in reported studies. [14][15][16] In our study, EEG was abnormal in 24% (33) patients. The seizure recurrence rate was statistically higher in patients with abnormal EEG and cranial MRI findings.…”
Section: Discussionsupporting
confidence: 49%